Cycloferon and Management of Herpes Virus Infection - L. M. Alimbarova (Антибиотики и Химиотерапия, 2020)
The treatment of patients with various forms of herpes requires a complex approach with using chemo- and immunotropic drugs. The use of Cycloferon, an interferon inductor (12.5% injection solution, 150 mg tablets or 5% liniment) was shown efficient. It had antiviral and immunotropic action in the mono- and combination therapy of herpes simplex of the skin and mucosa, genital herpes, ophthalmoherpes, herpes zoster, infectious mononucleosis. Cycloferon lowered the level and period of the disease clinical signs, prolonged the remission, corrected the immunity shifts, prevented the complications. The results of the study presented a conclusive proof for recommending such a use of Cycloferon in wide medical practice.